Pregnant bodies, puerperium, parenting, writing and the utopian power of words in Christa Wolf and Elena Ferrante (El Taco en la Brea, 2025)
The proposal is based on a comparative analysis of the representations of pregnant bodies, puerperium and parenting present in the novel The Quest for Christa T. of Christa Wolf and Elena Ferrante’s neapolitan tetratology which includes the novels: My Brilliant Friend (2011), The Story of a New Name (2012); Those who Leave and Those who Stay (2013) and The Story of the Lost Child (2014). Besides, it is intended to explore how from these works a reflection emerges on writing and the inadequacy of language to give an account of the experience that mother figures go through and that is inscribed in the utopian aspect of the power of the word to recover the female genealogy. The comparison aims to deepen the hypotheses of recent studies that focus on outlining a continuity between Wolf and Ferrante.
Keywords: Christa Wolf; Elena Ferrante; pregnant bodies; puerperium; utopian writing